The Root Canal Biofilm - Chávez de Paz, Luis E.; Chávez de Paz, Luis E.; Sedgley, Christine M.; Sedgley, Christine M.; Kishen, Anil.; Kishen, Anil. (Springer Series on Biofilms, 2015)
This book presents the current state of research on the basic scientific aspects of root canal biofilm biology within a clinically applicable context. Root canal biofilms are complex polymicrobial structures adhering to the root canal surface that are formed by microorganisms invading the pulpal space of teeth, and are associated with persistent root canal infections. Concerted efforts to study root canal biofilms have been made in the past decade, resulting in the publication of observational and experimental studies that detail the morphology and biology of these structures in infected root canals. In addition to confirming that bacteria in root canals do not exist in free-floating planktonic states as previously assumed, this new information on root canal biofilm infections has provided an opportunity to re-evaluate conventional clinical protocols and improve endodontic therapeutic measures. .